PENGARUH PENERAPAN PENDEKATAN RECIPROCAL TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN MODEL PADANG - Syamsuarni, Helda; Harisman, Yulyanti; Suryani, Mulia (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was background by learning activity and mathematics conceptual understanding the students still low where students more understood explanation their friends than teacher. This research was aimed to description development of mathematics students activity and to knew whether the mathematics conceptual understanding of the students by using Reciprocal Teaching approachment better than that of students by using the conventional learning in class VIII of MTsN Model Padang. This was an experimental research which used random toward the subject design. The data analysis using t-test assisted with MINITAB was found that Â greater than and P-value less than Î± value. This result signified that H0 was rejected. Thus, it was concluded that the mathematics conceptual understanding of the students by using Reciprocal Teaching approachment better than that of students by using the conventional learning. Whereas the development of mathematics students activity using Reciprocal Teaching approachment as generally was increased in each meeting.